2016
DOI: 10.1080/23294515.2016.1207724
|View full text |Cite
|
Sign up to set email alerts
|

Better to know than to imagine: Including children in their health care

Abstract: The ethical imperative for inclusion of children in their health care choices was not so much determined by the right for self-determination, but by the need to include them. If children are excluded, they imagine things, become more isolated, and are left alone with their fears. Nevertheless, the urge to protect children is innate, as adults often underestimate children's coping capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 42 publications
4
52
1
3
Order By: Relevance
“…This information enabled us to exclusively search for children that met the inclusion criteria (note: SCCR includes information on both living and deceased paediatric oncology cases and reports data on adolescents up to 20 years of age). This study confined their analysis to children who died due to childhood cancer in response to our previous project on children's inclusion in treatment‐related decision‐making in which we were unable to recruit palliative cases due to hesitancy to bring up this issue within discussions with families (Ruhe, Badarau et al., ; Ruhe, Wangmo et al., ; Wangmo, De Clercq et al., ; Wangmo, Ruhe et al., ). Therefore, to examine decision‐making regarding palliative care we decided to exclusively analyse medical records of deceased children.…”
Section: Methodsmentioning
confidence: 99%
“…This information enabled us to exclusively search for children that met the inclusion criteria (note: SCCR includes information on both living and deceased paediatric oncology cases and reports data on adolescents up to 20 years of age). This study confined their analysis to children who died due to childhood cancer in response to our previous project on children's inclusion in treatment‐related decision‐making in which we were unable to recruit palliative cases due to hesitancy to bring up this issue within discussions with families (Ruhe, Badarau et al., ; Ruhe, Wangmo et al., ; Wangmo, De Clercq et al., ; Wangmo, Ruhe et al., ). Therefore, to examine decision‐making regarding palliative care we decided to exclusively analyse medical records of deceased children.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from the study reported that while children generally value their involvement and find it important to be informed, they differ in their preferred level of involvement (Ruhe et al, ). Another manuscript from the project concluded that parents and physicians value child participation, but without explicitly referring to their right of self‐determination (Wangmo & De Clercq et al, ). They expressed the concern that children, as the affected persons, have the need to know.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is motivated by another crucial finding from our study. The shift from curative to palliative care was cited by all participants as a major reason to enhance the child's role in the decision‐making process; on the other hand it was identified as one of the main reasons to exclude them out fear that it would affect their morale (Wangmo & De Clercq et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several benefits have been found to relate to children′s participation in health care, such as feeling valued and feelings of greater control and less anxiety (Coyne, ; Coyne & Gallagher, ; Dixon‐Woods, Anwar, Young, & Brooke, ). It is clear that there is an increasing awareness of the benefits of child participation, yet it appears that children are rarely or inconsistent involved in healthcare processes (Coyne, ; Koller, ; Virkki, Heino Tolonen, Koskimaa, & Paavilainen, ) and that barriers exists for patient participation in the paediatric healthcare context (Ruhe et al., ; Wangmo et al., ). Moreover, it has been questioned whether the concept of participation has been fully implemented in healthcare organizations (Coyne & Gallagher, ).…”
Section: Introductionmentioning
confidence: 99%